2021
DOI: 10.1523/jneurosci.1701-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Analysis in AdultC. elegansReveals State-Dependent Alteration of Neural and Behavioral Responses

Abstract: Sleep, a state of quiescence associated with growth and restorative processes, is conserved across species. Invertebrates including the nematode Caenorhabditis elegans exhibit sleep-like states during development, satiety, and stress. Here, we describe behavior and neural activity during sleep and awake states in adult C. elegans hermaphrodites using new microfluidic methods. We observed effects of fluid flow, oxygen, feeding, odors, and genetic perturbations on lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Microorganisms inhabiting different ecological niches likely evolved divergent strategies for sensorimotor integration, despite conserved cilia-based motility. For example, CR swims according to a more continuous repertoire, whereas PO motility was episodic or excitable, fluctuating stochastically between fast swimming and behavioural quiescence, reminiscent of transitions between ‘wakeful’ and ‘sleep states’ observed in many animals [46]. Future work should seek to map the shape space of permissible ciliary waveforms [35] and any multiciliary actuation patterns [6], to the resulting species-specific motility behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms inhabiting different ecological niches likely evolved divergent strategies for sensorimotor integration, despite conserved cilia-based motility. For example, CR swims according to a more continuous repertoire, whereas PO motility was episodic or excitable, fluctuating stochastically between fast swimming and behavioural quiescence, reminiscent of transitions between ‘wakeful’ and ‘sleep states’ observed in many animals [46]. Future work should seek to map the shape space of permissible ciliary waveforms [35] and any multiciliary actuation patterns [6], to the resulting species-specific motility behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…For a similar understanding of sleep architecture in C. elegans , it will be useful to observe both muscle and neuronal activity in animals that show the hallmarks of sleep. Lawler and colleagues have begun these studies and verified that sleeping worms show a more flaccid posture, though they twitch the anterior portions of their body during bouts of spontaneous sleep (Lawler et al ., 2021). Detailed analysis of calcium currents in post-training sleep may allow us to better understand sleep architecture in memory consolidating animals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, synaptic transmission at GABAergic neuromuscular junctions decreased in animals sleeping during developmental lethargus, but UNC-49 GABA receptor immunostaining was not reduced (Dabbish and Raizen, 2011). Studies of unrestrained, sleeping animals showed that the neural dynamics of the AVA backward command neuron is severely blunted, while AWA, an appetitive sensory neuron that has an ON response, rather than an OFF response like AWCs, has a prolonged response to odor when sleeping (Lawler et al, 2021). A similar analysis of the AWC sensory circuit during post-training sleep is required to understand the neural dynamics in the sleeping worm, so that the relationship between neuronal activity and synapse size can be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This closed-loop system is flexible and can be configured to detect any visible events, such as behavior patterns or optical reporters, and measure corresponding evoked neural responses. For complete details on the use and execution of this protocol, please refer to Lawler et al. (2021) .…”
mentioning
confidence: 99%
“…For complete details on the use and execution of this protocol, please refer to Lawler et al. (2021) .…”
mentioning
confidence: 99%